An Unusual TEN-Like Presentation of Juvenile Bullous Pemphigoid: A Diagnostic Challenge. (11th April 2022) - Nikyar, Zahra; Hatami, Parvaneh; Aryanian, Zeinab; Sotoudeh, Soheila; Ziaee, Vahid; Goodarzi, Azadeh
Abstract : Bullous pemphigoid (BP) is an acquired autoimmune bullous disorder rarely seen in the pediatric population. It usually presents as large and tense bullae, predominantly distributed in the acral areas. Herein, we describe a case of childhood BP with an atypical presentation mimicking toxic epidermal necrolysis (TEN). This case shows us that juvenile BP should be considered in the differential diagnosis of TEN in children, particularly if there are unusual features and an intractable course.